Individual Risk Attitude: Measurement and Determinants -- An empirical study from China - Hu, Zengbao (2018)
This paper serves the purpose of measuring individual risk attitude of Chinese people and investigating its determinants. The results are compared to the previous researches done in the West in order to consider individual risk attitude from a cross-cultural perspective. This paper measures individual risk attitude and explores its determinants by conducting a face-to-face questionnaire survey with 7-point Likert scale questions. Then the outcomes are analyzed using various quantitative research methods including correlation analysis, linear regression analysis, and factor analysis. This paper concludes that most individuals are risk averse. Risk attitude is domain-specific and varies across contexts. Negative correlations are found between risk attitudes in some domains, and the theory of risk capacity constraint is proposed in this paper to account for such a phenomenon. Besides, collectivism, as a cultural factor, could shape individual risk attitude in some domains. In addition, there are differences between Chinese and Westerns in terms of individual risk attitudes and their determinants. This paper has proposed some possible explanations for such national differences. This paper has also raised some new questions that future researches could explore and provides some suggestions on how future researches might do differently to help shed more light on this topic.